Tutto quello che vuoi - Bruni, Francesco 1961-; Montaldo, Giuliano 1930-2023; Carpenzano, Andrea; Bruni, Arturo (01 Distribution, 2017)
Alessandro is an ignorant and turbulent twenty-two year old. Giorgio (Giuliano Montaldo) an eighty-five-year-old forgotten poet. The two meet when Alessandro accepts a job as a companion of that elegant gentleman in afternoon walks. With the passage of days, the poet progressively evokes a remembrance of his remote past: the hints of a real treasure hunt. Following them, Alexander will venture together with Giorgio on a journey to discover that hidden wealth, and that concealed in his own heart
Film released April 2017
Keywords: Intergenerational relations / Italy / Drama; Intergenerational relations; Italy; Feature films; Comedy plays; Video recordings for the hearing impaired; Drama; DVD-Video discs; Film; DVD-Video